2019
DOI: 10.1002/cne.24688
|View full text |Cite
|
Sign up to set email alerts
|

Molecular architecture of the zebra finch arcopallium

Abstract: The arcopallium, a key avian forebrain region, receives inputs from numerous brain areas and is a major source of descending sensory and motor projections. While there is evidence of arcopallial subdivisions, the internal organization or the arcopallium is not well understood. The arcopallium is also considered the avian homologue of mammalian deep cortical layers and/or amygdalar subdivisions, but one‐to‐one correspondences are controversial. Here we present a molecular characterization of the arcopallium in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(94 citation statements)
references
References 125 publications
(335 reference statements)
8
86
0
Order By: Relevance
“…In mammals, these nuclei are specifically targeted by neurons from cortical layer V. Like layer V neurons, the AI also gives rise to long‐range descending projections to the midbrain tectum and tegmentum, as well as to the lateral pons. Furthermore, recent receptor and gene expression studies have shown a close similarity between regions of the arcopallium, including AI, and cortical layer V–VI cell populations (Chen et al, ; Dugas‐Ford et al, ; Jarvis et al, ; Mello et al, ; Pfenning et al, ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In mammals, these nuclei are specifically targeted by neurons from cortical layer V. Like layer V neurons, the AI also gives rise to long‐range descending projections to the midbrain tectum and tegmentum, as well as to the lateral pons. Furthermore, recent receptor and gene expression studies have shown a close similarity between regions of the arcopallium, including AI, and cortical layer V–VI cell populations (Chen et al, ; Dugas‐Ford et al, ; Jarvis et al, ; Mello et al, ; Pfenning et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…(Atoji, Saito, & Wild, 2006;Cohen, 1975;Herold, Paulitschek, Palomero-Gallagher, Güntürkün, & Zilles, 2018;Jarvis et al, 2005;Jarvis et al, 2013;Kröner & Güntürkün, 1999;Reiner et al, 2004;Schriber, 1978;Veenman, Wild, & Reiner, 1995;Wynne & Güntürkün, 1995). An additional ventral arcopallial division (AV) combines "viscerolimbic" molecular characteristics with connectional properties related to sensory, associative processing (Herold et al, 2018;Mello, Kaser, Buckner, Wirthlin, & Lovell, 2019;Shanahan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We found that most AId neurons were selective for single movements or for different AId of anesthetized zebra finches elicits increased spontaneous firing rates, and parvalbumin expression is higher in AId compared to surrounding motor cortex (Mello et al, 2019;Yuan and Bottjer, 2019). Similarly, mammalian motor cortex contains a substantial population of inhibitory interneurons, which have been implicated in both regulating plasticity during motor skill learning and coordinating activity across motor cortex during behavior (Jacobs and Donoghue, 1991;Hess and Donoghue, 1994;Hess et al, 1996;Markram et al, 2004;Stagg et al, 2011;Donato et al, 2013;Chen et al, 2015;Kida et al, 2016;Adler et al, 2019).…”
Section: Heterogeneous Activity Within Aid Suggests Multi-dimensionalmentioning
confidence: 90%
“…The RA is considered part of the intermediate arcopallium, which is the major source of descending output from the avian telencephalon 38 . The arcopallium, more broadly, is thought to contain the avian analog of the deep layers of the mammalian sensory and motor cortices based on similarities in their projection patterns 31 , 39 , neuronal activation 33 , 40 , and transcriptional profiles 41 44 , but may also contain the avian equivalent of pallial parts of the mammalian amygdala 44 46 . Avian analogs of RA are found in other birds that evolved vocal learning 9 13 , but are thought to be absent in vocal non-learning birds based on cytoarchitectonics and molecular criteria 14 – 16 , 47 ; but see also 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%